Gibberellin Signaling in Plants – The Extended Version - Schwechheimer, Claus (Frontiers in Plant Science, 2012)
The plant hormone gibberellin (GA) controls major aspects of plant growth such as germination, elongation growth, flower development and flowering time. In addition, a number of studies have in recent years allowed to unravel less apparent roles of GA in a surprisingly broad set of developmental as well as cell biological processes. The identification of GA receptor proteins on the one end of the signalling cascade and transcription regulators such as the PHYTOCHROME INTERACTING FACTORS and the GATA-type transcription factors GNC and CGA1/GNL on the (current) other end of the signalling cascade have extended our knowledge about how GA exerts its function as a regulator and about how this hormone may regulate a diverse set of plant responses.